The Effects of Helicobacter pylori Infection on Gastric Microbiota in Children With Duodenal Ulcer - Zheng, Wei; Zhu, Zhenya; Ying, Jingjing; Long, Gao; Chen, Bo; Peng, Kerong; Li, Fubang; Zhao, Hong; Jiang, Mizu (Frontiers in Microbiology, 2022)
Background: Helicobacter pylori infection is the main cause of chronic gastritis and duodenal ulcer in children. Little is known about the effect of Helicobacter pylori on gastric microbiota in children with duodenal ulcer. This study was aimed at the characterisitcs of gastric microbiota in children with duodenal ulcer on Helicobacter pylori infection. Methods: We studied 23 children diagnosed with duodenal ulcer by gastric endoscopy due to gastrointestinal symptoms, 15 cases were diagnosed with Helicobacter pylori infection，while 8 cases without Helicobacter pylori infection. Endoscopic mucosal biopsy samples were obtained for DNA extraction. Microbiomes were analyzed by 16S rRNA profiling and microbial functions were predicted using the software PICRUSt. Results: Bacterial richness and diversity of gastric microbiota in duodenal ulcer with Helicobacter pylori-positive were lower than those negative. The gastric microbiota in Helicobacter pylori-positive group significantly reduced proportions of six phyla and fifteen genera; only Helicobacter taxa were more abundant in Helicobacter pylori-negative group. Co-expression network analysis showed a more complex network of interactions in Helicobacter pylori-positive group than that in Helicobacter pylori-negative group. For predicted functions, lower abundance in the pathways of carbohydrate metabolism, signal transduction, amino acid metabolism and lipid metabolism were found in Helicobacter pylori-positive group than Helicobacter pylori-negative group. H. pylori colonization reduces a microbial community with genotoxic potential in the gastric mucosa of children with duodenal ulcer. Conclusions: Presence of Helicobacter pylori significantly influences gastric microbiota and results in lower abundance of multiple taxonomic levels in children with duodenal ulcer. Children with duodenal ulcer exhibit a dysbiotic microbial community with genotoxic potential, which is distinct from that of children with or without Helicobacter pylori infection.